Reducing Brain Signal Noise in the Prediction of Economic Choices: A Case Study in Neuroeconomics - Sundararajan, Raanju R.; Palma, Marco A.; Pourahmadi, Mohsen (Frontiers in Neuroscience, 2017)
In order to reduce the noise of brain signals, neuroeconomic experiments typically aggregate data from hundreds of trials collected from a few individuals. This contrasts with the principle of simple and controlled designs in experimental and behavioral economics. We use a stationary subspace analysis (SSA) to filter out the noise (nonstationary sources) in EEG brain signals. The nonstationary sources in the brain signal are associated with variations in the mental state that are unrelated to the experimental task. SSA is a powerful tool fo reducing the number of trials needed from each participant in neuroeconomic experiments and also for improving the prediction performance of an economic choice task. For a single trial, when SSA is used as a pre-processing technique, the prediction model in a food snack choice experiment has an increase in overall accuracy by around 10-12% and in sensitivity and specificity by around 20%.